SISTEM PENDUKUNG KEPUTUSAN PENENTUAN KARYAWAN KONTRAK MENJADI KARYAWAN TETAP MENGGUNAKAN METODE SAW (STUDI KASUS : PT. SEMESTA CITRA MEDIA) - Fitra Akbar Nurarviansyah; Khaerul Ma'mur (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
Abstract− Every company needs employees as workers who carry out every activity in the company organization, contract employees and permanent employees. Contract employees are employees who are only hired when the company needs additional workers who operate manually, while permanent employees are employees who have contracts or work agreements with the company for an indefinite period of time (permanent). Permanent employees usually tend to have far greater rights than non-permanent employees. PT. Semesta Citra Media (SCMedia) is a national private company that is engaged in the field of telecommunication networks with a focus on providing services and devices based on VSAT IP. SCMedia was founded in early 2003. The SAW method is often also known as the weighted sum method. The basic concept of the SAW method is to find the weighted sum of the performance ratings for each alternative on all attributes. The SAW method requires a process of normalizing the decision matrix (X) to a scale that can be compared with all existing alternative ratings. Assessment of data for hiring employees was successfully carried out with the following results, namely A8 by having the best alternative by having criteria, namely work experience: 4, discipline: 91, loyalty: 76, age: 24, and performance: 78, with these results then A8 (Anugrah Rafi) is entitled to be appointed as a permanent employee. To determine the feasibility of the criteria used in hiring employees, the authors use the following criteria: work experience, discipline, loyalty, age, and performance in determining employee appointments.Keywords: SPK, Simple Additive Weighting, Employee Recruitment